2022
DOI: 10.3390/agronomy12040841
|View full text |Cite
|
Sign up to set email alerts
|

Can Cold Plasma Be Used for Boosting Plant Growth and Plant Protection in Sustainable Plant Production?

Abstract: Sustainable agriculture with low inputs of chemicals and fertilizers has been recently attracting more attention from producers and researchers in the EU. The main reason for such attention is The European Green Deal—the EU’s latest growth strategy concerning environmental degradation and climate change. One of its main components is the Farm to Fork strategy, which especially features the reduction in pesticide and mineral fertilizer application and also supports the development of organic farming. At the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 171 publications
1
22
0
1
Order By: Relevance
“…Hence a sustainable technology with less energy consumption and reduced chemical fertilizer use are of interest to researchers and producers to meet the demands. 171 Cold plasma has the potential to be used as a green fertilizer in the future due to its increased efficiency and eco-friendly production. As the plasma treatment will lead to the production of reactive oxygen species and reactive nitrogen species in water, it acts as a fertilization liquid facilitating plant development.…”
Section: Cold Plasma As Green Fertilizermentioning
confidence: 99%
“…Hence a sustainable technology with less energy consumption and reduced chemical fertilizer use are of interest to researchers and producers to meet the demands. 171 Cold plasma has the potential to be used as a green fertilizer in the future due to its increased efficiency and eco-friendly production. As the plasma treatment will lead to the production of reactive oxygen species and reactive nitrogen species in water, it acts as a fertilization liquid facilitating plant development.…”
Section: Cold Plasma As Green Fertilizermentioning
confidence: 99%
“…Mivel ez a fizikai tényező ionok, atomok, elektronok, gyökök és molekulák összetett keveréke, a növényekre és kórokozókra gyakorolt hatása is összetett. Pańka et al (2022) a szakirodalom feltárása során bizonyítékokat talált a nem termikus plazma lehetséges felhasználására a növénynövekedés fokozására és a növényvédelemre.…”
Section: Szakirodalmi Feldolgozásunclassified
“…Direct treatment of seeds and the use of PAW for irrigation are potential applications of ACP in agriculture. In 2022, a comprehensive review, Panka and collaborators reported about the use of cold plasma in sustainable seed production, and plant growth improvement [75]. While their study outlines some of the most relevant contributions in the field of cold plasma technology, it focuses heavily on the plant and seed aspects of the agricultural chain, and unfortunately does not provide major details on the latest developments of technologies in use for food processing applications, nor does it mention the use of plasma-activated liquids, a key application currently highly researched, in agriculture and decontamination.…”
Section: Cold Plasma In Agriculturementioning
confidence: 99%